Rabindranath Tagore’s Intellectual Legacy: Contributions to Educational and Cultural Modernity - Patil, Bharat (Journal of Educational Research and Policies, 2025)
Rabindranath Tagore: he was more than a poet - he was a philosopher, an educator, a visionary, an architect of the cultural and educational landscape of a nation on the rise, India, and the entire world. His philosophies on life, learning and humanism were groundbreaking in their time and remain relevant today. Tagore was philosophical sensibility toward education and society emphasized the relationship between individuals, nature, and the strider action of the planet. His thinking on freedom, creativity, and the holistic development of a person remains relevant and vital in today’s educational system.